Analyses of Visitors' Experiences in a Natural World Heritage Site Based on TripAdvisor Reviews. Issue 2 (3rd July 2019) - Stoleriu, Oana Mihaela; Brochado, Ana; Rusu, Alexandru; Lupu, Cristina
Abstract: Danube Delta is the second largest European delta, a UNESCO World Heritage Site, and a famous paradise for nature lovers and bird watchers, which attracts increasing numbers of tourists every year. The article uses mixed methods, qualitative (i.e., narratives) and quantitative (i.e., computer) analyses, to examine the main components of visitors' subjective experiences of the Danube Delta. Data is represented by online visitor reviews, posted between 2011 and 2017 on the TripAdvisor website. The results showed that experiences of the Danube Delta are mostly positive and centered on direct contact with nature and wildlife. However, managerial aspects linked to visit organization, such as boat types, trip itinerary, duration, or food, were more prominent in the tourists' impressions and recommendations, compared to destination attributes. Experiences of the Danube Delta are mostly passive, dominantly visual, with low visitor emotional and physical engagement. The cultural and environmental dimensions are underrepresented in people's reviews.